Church and Civil Society : German and South African perspectives (Sun Press, 2017)
Germany and South Africa experienced drastic social transitions with the fall of the Berlin Wall in 1986 and the end of Apartheid in 1994. This book consists of a collection of essays from German and South African theologians who analyse the role that religious communities had, and are still playing within the respective civil societies. The concept and texture of civil society are analysed; case studies are presented; theological perspectives are given on the relation between church, state and civil society; and guidelines are provided for the healing role that Christian religious communities can play in Germany and South Africa. This book is mainly directed at theologians and scholars in religious studies, however, sociologists and political philosophers may also find the essays informative. Besides the wide variety of theological approaches; sociological and empirical data; and practical theological perspective, the book also yields interesting comparative analysis on two societies in transition.